Optimalization Strategy for Corporate Social Responsibility (CSR) Programs Based on Community Empowerment Towards Economic Independence Post-Mining by the Gold Mining Business Unit of PT Antam Tbk. - Cindy Pricillia Octavenda; Teguh Iman Santoso (Cita konsultindo, 2024)
This study aims to evaluate the implementation, challenges, and strategies of PT Antam Pongkor's CSR program to enhance the economic independence of local communities. Using qualitative methods, this study produces interviews and data analysis to describe the situation. The sample was purposively selected, involving the company, village government, and CSR recipients. Data collection techniques included interviews, observation, and documentation, with semi-structured interviews used to obtain in-depth data. Triangulation methods were employed to verify the data through various approaches, including data sources, researchers, theories, and methods. The results indicate that PT Antam's CSR program needs to be more effective by adhering to the Triple Bottom Line principles (People, Planet, Profit). Recommended strategies include skills training in agriculture, livestock, and SMEs. The challenges faced include community dependency on the company, changes in funding, lack of community involvement, and limited resources. To address these issues, the company needs to develop empowerment programs, increase community engagement, and strengthen the monitoring and evaluation system.